PENGEMBANGAN E-MODUL PEMANASAN GLOBAL BERBASIS EDUCATION FOR SUSTAINABLE DEVELOPMENT UNTUK SEKOLAH DASAR - Berlianti W.M., Elca; Hamdu, Ghullam; Ramadhani Putri, Agnestasia (Attadib: Journal of Elementary Education, 2024)
His research is an development study intended to produce a product of the electronic teaching module based Education for Sustainbale Development for primary school students. Data collection techniques used by observation, interview and focus group discussion (FGD). Electronic modes have been validated by media and design experts, materials experts, and pedagogic experts and have been tested on students. Research shows the feasibility of the e-modules from the validated experts: At 3.89, 3.70 materials and pedagogists at 3.48 in excellent category. E-module worthiness assessment results based on student responses of 3.66 from Max score 4. This proves that the e-modules are worthy of being used as a self-sufficient teaching supplement to students.